Los riesgos financieros en la Cartera de Crédito de la COAC UNIBLOCK y SERVICIOS Ltda., periodo marzo-diciembre 2020. - Herrera Pérez, Karen Estefanía (2022)
The Savings and Credit Cooperatives play an important role in the financial activity of Ecuador, seeking to capture savings and support their members with loans for new ventures at reasonable rates, framed in the solidarity economy as non-profit entities. This research project with the theme: “Financial Risk in the credit portfolio of COAC. Uniblock y Servicios Ltda., period March – December 2020”, was elaborated with the objective of analyzing the financial risks in the credit portfolio in the period March – December, using the deductive method which goes from general to particular knowledge, field and documentary through surveys, seeking the verification of the hypothesis through the chi-square the Person’s gyving viability to the study, then the analysis of the indicators of effectiveness and efficiency was performed. The CAMELS methodology was also used to identify financial risks. The study concludes by identifying the causes that trigger financial risks in the credit portfolio, in the cooperative, credit and legal areas; these being payment analysis, verification of documents, and inadequate administration of the credit granted. It was also identified that in spite of following up with the delinquent members and establishing strategies, on certain occasions 100% compliance is not achieved, due to the lack of continuous follow-up with the delinquent member and the inadequate application of processes. In addition, it was verified that during the period of analysis the COVID-19 pandemic affected the country’s economy